Quality of care for acute ischemic stroke in China during the COVID-19 pandemic: a retrospective study using a National database - Ruize Guo; Jingkun Li; Mengyang Liu; Meina Liu (BMC Public Health)
Abstract Background Acute ischemic stroke (AIS) is one of the most time-sensitive diseases, which requires prompt medical services. Delayed treatment and resource scarcity during the coronavirus disease 2019 (COVID-19) pandemic may affect the quality of AIS care and increase the risk of adverse outcomes for patients. Methods The study used data from China’s National Medical Quality Database spanning from January 1, 2019, to May 31, 2022. Quality of care was gauged utilizing 15 indicators, featuring 12 quality indicators (QIs) and 3 composite indicators. We used mixed-effects and interrupted time series models to compare care quality pre- and post-pandemic. Utilization rates of 15 indicators were compared across different age and gender groups to evaluate healthcare disparities. Multilevel Logistic regression and structural equation modeling assessed the impact of the 3 composite indicators on outcome (in-hospital mortality or 30-day readmission) during the pandemic. Results Utilization rates for 10 of 12 QIs and three composite indicators declined rapidly after the COVID-19 outbreak, but later improved. The most significant drop was observed for rehabilitation (QI12), with a decrease of 50.06% (P < 0.0001). The overall treatment quality (Score) showed a decrease of -14.44% (95% CI -15.62% to -13.26%; P < 0.0001), and experienced a long-term trend change of 0.58 (95% CI 0.40 to 0.75; P < 0.0001). Female patients had lower rates for 11 QIs and all composite indicators compared with male patients, with the greatest difference noted in dysphagia screening (66.45% vs. 69.87%, P = 0.0472). Patients aged 75 years or older had lower rates for 9 QIs and all composite indicators compared with other age groups, with the greatest difference in anticoagulation therapy (difference = 10.01%, P < 0.0001). High-quality care was significantly associated with lower rates of adverse outcomes (OR = 0.965; 95% CI 0.962 to 0.968; P < 0.0001). Conclusions The COVID-19 outbreak has deepened the gap between optimal care and clinical practice, which then gradually improved. During the pandemic, high-quality care was important to reduce the risk of adverse outcomes, but there were gender and age differences in the provision of health-care quality.